2021
DOI: 10.1093/glycob/cwaa119
|View full text |Cite
|
Sign up to set email alerts
|

Glyco-engineered HEK 293-F cell lines for the production of therapeutic glycoproteins with humanN-glycosylation and improved pharmacokinetics

Abstract: N-glycosylated proteins produced in human embryonic kidney 293 (HEK 293) cells often carry terminal N-acetylgalactosamine (GalNAc) and only low levels of sialylation. On therapeutic proteins, such N-glycans often trigger rapid clearance from the patient's bloodstream via efficient binding to asialoglycoprotein receptor (ASGP-R) and mannose receptor (MR). This currently limits the use of HEK 293 cells for therapeutic protein production. To eliminate terminal GalNAc, we knocked-out GalNAc transferases B4GALNT3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…Studies have shown that FAM83D is strongly associated with cancer development, proliferation, invasion, and metastasis ( 78 , 79 ). Beta-1,4-N-acetylgalactosaminyltransferase 4 (B4GALNT4), as an N-acetylgalactosamine transferase, is involved in the post-translational regulation of genes through protein glycosylation modifications ( 80 ). B4GALNT4 is upregulated in various cancers, and its expression can enhance the malignant potential of cancers ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FAM83D is strongly associated with cancer development, proliferation, invasion, and metastasis ( 78 , 79 ). Beta-1,4-N-acetylgalactosaminyltransferase 4 (B4GALNT4), as an N-acetylgalactosamine transferase, is involved in the post-translational regulation of genes through protein glycosylation modifications ( 80 ). B4GALNT4 is upregulated in various cancers, and its expression can enhance the malignant potential of cancers ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recently developed glycoengineered HEK293-F cell line eliminates terminal GalNAc glycosylation and increases sialylation due to the knockout of GalNAc transferases B4GALNT3 and B4GALNT4 and overexpression of sialyltransferases ST6GAL1 and ST3GAL6. This glycoengineered cell line is well-suited for the production of therapeutic proteins with fully human N-glycosylation profile and superior pharmacokinetic properties [69].…”
Section: Expression Systems and Approaches To Production Of Bispecifi...mentioning
confidence: 99%
“…Sialyl Lewis X is a member of blood carbohydrates present on the surface of different immune cells; it is a ligand for selectins and play an important role in different physiological phenomena [82,83]. Moreover, antennae fucosylation is also correlated with the rapid clearance and cellular uptake mediated by the mannose receptor present on macrophages and dendritic cells [8,84]. Antennae fucosylation can therefore increase the clearance and likely immunogenicity.…”
Section: Antennae Fucosylationmentioning
confidence: 99%